Use of Salivary Iodine Concentrations to Estimate the Iodine Status of Adults in Clinical Practice - Dekker, Bernadette L; Touw, Daan J; van der Horst-Schrivers, Anouk N A; Vos, Michel J; Links, Thera P; Dijck-Brouwer, D A Janneke; Kobold, Anneke C Muller (The Journal of nutrition, 2021)
ABSTRACT Background Measurement of the 24-h urinary iodine concentration or urinary iodine excretion (UIE) is the gold standard to determine iodine status; however, this method is inconvenient. The use of salivary iodine could be a possible alternative since salivary glands express the sodium-iodine symporter. Objectives We aimed to establish the correlation between the salivary iodine secretion and UIE, to evaluate the clinical applicability of the iodine saliva measurement. Methods We collected 24-h urine and saliva samples from 40 participants ≥18 y: 20 healthy volunteers with no specific diet (group 1), 10 patients with differentiated thyroid cancer with a low dietary intake (<50 μg/d, group 2), and 10 patients with a high iodine status as the result of the use of amiodarone (group 3). Urinary and salivary iodine were measured using a validated inductively coupled plasma MS method. To correct for differences in water content, the salivary iodine concentration (SIC) was corrected for salivary protein and urea concentrations (SI/SP and SI/SU, respectively). The intra- and inter-individual CVs were calculated, and the Kruskal-Wallis test and Spearman's correlation were used. Results The intra-individual CVs for SIC, SI/SP, and SI/SU were 63.8%, 37.7%, and 26.9%, respectively. The inter-individual CVs for SIC, SI/SP, and SI/SU were 77.5%, 41.6% and 47.0%, respectively. We found significant differences (P < 0.01) in urinary and salivary iodine concentrations between all groups [the 24-h UIE values were 176 μg/d (IQR, 96.1–213 μg/d), 26.0 μg/d (IQR, 22.0–37.0 μg/d), and 10.0*103 μg/d (IQR, 7.57*103–11.4*103 μg/d) in groups 1–3, respectively; the SIC values were 136 μg/L (IQR, 86.3–308 μg/L), 71.5 μg/L (IQR, 29.5–94.5 μg/L), and 14.3*103 μg/L (IQR, 10.6*103–25.6*103 μg/L) in groups 1–3, respectively]. Correlations between the 24-h UIE and SIC, SI/SP, and SI/SU values were strong (ρ = 0.80, ρ = 0.90, and ρ = 0.86, respectively; P < 0.01). Conclusions Strong correlations were found between salivary and urinary iodine in adults with different daily iodine intakes. A salivary iodine measurement can be performed to assess the total iodine body pool, with the recommendation to correct for salivary protein or urea.